2000
DOI: 10.1152/jappl.2000.88.6.2227
|View full text |Cite
|
Sign up to set email alerts
|

Aortic input impedance in infants and children

Abstract: Flow and pressure measurements were performed in the ascending aortas of six pediatric patients ranging in age from 1 to 4 yr and in weight from 7.2 to 16.4 kg. From these measurements, input impedance was calculated. It was found that total vascular resistance decreased with increasing patient weight and was approximately one to three times higher than those of adults. Conductance per unit weight was relatively constant but was approximately three times higher than for adults. Strong inertial character was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 17 publications
3
33
1
1
Order By: Relevance
“…Previous investigators, using more invasive cuff-type flow probes, have identified these as useful parameters of vascular function. [23][24][25][26][27][28] …”
Section: Discussionmentioning
confidence: 99%
“…Previous investigators, using more invasive cuff-type flow probes, have identified these as useful parameters of vascular function. [23][24][25][26][27][28] …”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have introduced an inertance in series with the characteristic impedance [4,5,7,25,32,57]. This series inertance does not affect the arterial input impedance at low frequencies but at high frequencies.…”
Section: The Four-element Windkesselmentioning
confidence: 99%
“…Unreliability of arterial inertance representation can explain why the W4P fell short when applied by Sharp et al [17] to interpret pressureÀflow relationships in infants and children, who show aortic impedance data with much stronger inertial character than adults. Better impedance approximation was obtained by these authors from an alternative four-element model derived from the W3 by connecting L in series with R c (W4S model, Figure 21.4).…”
Section: Four-element Modelsmentioning
confidence: 99%
“…Better impedance approximation was obtained by these authors from an alternative four-element model derived from the W3 by connecting L in series with R c (W4S model, Figure 21.4). From W4S parameter estimates, Sharp et al [17] inferred that significant changes are in progress during vascular development from infancy to adulthood. In particular, a significant difference was observed in the development rate of R c and R p , such that a rapid reduction characterized the R c /R p ratio during early development.…”
Section: Four-element Modelsmentioning
confidence: 99%